A thousand ways to die: exceptional preservation of sea stars on a paleosurface from La Meseta Formation (Eocene, Antarctic Peninsula) - Palópolo, Evangelina Elizabeth (2018)
Fil: Palópolo, Evangelina. Universidad Nacional de Río Negro, Instituto de investigación en Paleobiología y Geología. Río Negro, Argentina.